Lexicography of Coronavirus-Related Neologisms. - Klosa-Kückelhaus, Annette; Kernerman, Ilan. (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The series features monographs and edited volumes on the topics of lexicography and meta-lexicography. Works from the broader domain of lexicology are also included if they strengthen the theoretical, methodological and empirical basis of lexicography and meta-lexicography. Thevolumes focus on aspects of lexicography such as micro- and macrostructure, typology, history of the discipline, and application-oriented lexicographical documentation.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books